2001
DOI: 10.1046/j.1365-3083.2001.00882.x
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Cell‐Mediated Immunity Following Immunization with Pneumococcal Conjugate or Polysaccharide Vaccine*

Abstract: The immunogenicity of pneumococcal polysaccharide (PS) vaccines can be improved by conjugating PS to a polypeptide carrier that alters the immune response from T-cell independent to T-cell dependent. In order to study the influence of PS or protein antigens as inducers of cell-mediated responses, 30 adults were immunized with a 23-valent pneumococcal PS vaccine (PS-group) or an 11-valent, tetanus and diphtheria mixed carrier conjugate vaccine with (adjuvant group) or without aluminium adjuvant (nonadjuvant gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
22
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 28 publications
4
22
1
Order By: Relevance
“…Conversely, the 23-valent pneumococcal polysaccharide vaccine produces a humoral response: inducing the production of antibody from B lymphocytes in the absence of help from T lymphocytes. This vaccine does not induce interferon-gamma or interleukin-4 and interleukin-5 cytokines related to T lymphocytes (7). The levels of complement C3 and C4 are reported to reveal no change after a 23-valent pneumococcal polysaccharide vaccination (8) and the present patient revealed the same results.…”
Section: Discussionsupporting
confidence: 68%
“…Conversely, the 23-valent pneumococcal polysaccharide vaccine produces a humoral response: inducing the production of antibody from B lymphocytes in the absence of help from T lymphocytes. This vaccine does not induce interferon-gamma or interleukin-4 and interleukin-5 cytokines related to T lymphocytes (7). The levels of complement C3 and C4 are reported to reveal no change after a 23-valent pneumococcal polysaccharide vaccination (8) and the present patient revealed the same results.…”
Section: Discussionsupporting
confidence: 68%
“…It is assumed that the increased immunogenicity of PS antigens after conjugation to proteins is due to the induction of carrier-specific T cells that provide help to B cells that have internalized and processed the PS conjugate complex and presented peptides of the carrier in MHC class II molecules [40]. Induction of carrier-specific T cells after immunization with conjugate vaccines has been demonstrated both in mice [10,13], human adults ( [11,12] and Ingolfsdottir, G. et al unpublished data) and children [41]. Furthermore, it has been demonstrated that co-stimulatory signals through CD28-B7, and interaction between CD40-CD40L is required for optimal PS-specific B-cell responses after immunization with conjugate vaccines [14].…”
Section: Discussionmentioning
confidence: 99%
“…The absence of T cell help in Ab responses to PS is due to their inability to associate with MHC class II molecules on APC [8,9]. However, conjugation of PS to protein carriers allows T cell help through recruitment of carrier-specific T cells [10][11][12][13][14] and makes the PPS immunogenic in early infancy (reviewed in [15]). Protective immunity against both invasive disease [16,17] and otitis media [18] has been demonstrated after vaccination of infants with pneumococcal conjugate vaccines.…”
Section: Introductionmentioning
confidence: 99%
“…Wuorimaa et al found that in vitro stimulation of human peripheral blood cells with caps-PS induced activation of IFN-+ -secreting lymphocytes [23]. Caps-PS was also shown to induce IL-6 in in vitro cultured human lymphocytes [24].…”
Section: Discussionmentioning
confidence: 99%